The European Union’s global strategy: complementarity and specialization - Barroso, L.; Cruz, M. (Portuguese Journal of Social Science, 2019)
As a grand strategy, European Union Global Strategy (EUGS) is a roadmap to convert the European Union (EU) in a key strategic actor. The evidence of some conceptual vulnerabilities, particularly the EU lack of classical means and strategic autonomy, limits its implementation. Thus, this article aims to find some relevant actions that the EU needs to put in place to enhance her global image as a credible and specialized actor where the power of her strategic partners, as NATO and United Sates, need to be complemented. To that effect, first, the EU must demonstrate leadership and mobilize the support of member states to carry out its strategy. Second, it must leverage its strategic autonomy by intervening in crises and conflicts where the military means are not the most important. Third, it must focus on preventing or solving the problems in the EU’s neighbourhood as it will suffer direct repercussions if it fails to do so. Implementing the EUGS will require a generic but encompassing grand strategy concept; to communicate its achievements through annual reviews, laying a foundation upon which the EU can build its internal and external credibility, providing it with the strategic autonomy it so direly needs. Finally, the EU must invest on Europeanization processes by ‘transforming’ societies through the ‘global’ application of EU instruments.